Perilaku Sintaksis Kata Sifat dalam Bahasa Bali - Suryati, Ni Made; Mulyawati R., Tjok Istri Agung (Humanis; Vol 28 No 1 (2024), 2024)
This article is intended to analyze the syntactical behavior of adjectives in Balinese language at phrases and clauses level. The data were collected using the observation method and note-taking and recording techniques. The data were analyzed using the connecting and comparing techniques, and distributional method with deletion, transformational, and insertion techniques. The results of data analysis were formally and informally presented using both inductive and deductive techniques. The results of the study show that in the endocentric and attributive phrases, the adjectives in Balinese language function as the central and attributive elements, that in the endocentric and coordinative phrases, they function as the central element only, and that in the exocentric phrase, they function as the axis. The meaning of the phrase with an adjective + adjective construction refers to equivalence and opposition. In the clausal level, adjectives in Balinese language function as predicate, complement, and adverb.